On some new Hermite-Hadamard and Ostrowski type inequalities for s-convex functions in (p, q)-calculus with applications - You Xue-Xiao; Ali Muhammad Aamir; Kalsoom Humaira; Soontharanon Jarunee; Sitthiwirattham Thanin (Open Mathematics, 2022)
In this study, we establish some new Hermite-Hadamard type inequalities for s-convex functions in the second sense using the post-quantum calculus. Moreover, we prove a new (p,q)\left(p,q)-integral identity to prove some new Ostrowski type inequalities for (p,q)\left(p,q)-differentiable functions. We also show that the newly discovered results are generalizations of comparable results in the literature. Finally, we give application to special means of real numbers using the newly proved inequalities.